Respuesta :

ANSWER

[tex]x=-3,y=-1,z=-2[/tex]



EXPLANATION

The given equations are:

[tex]3x+4y-5z=-3--(1)[/tex]

[tex]-5x-2y+6z=5--(2)[/tex]

and

[tex]4x-8y+3z=-10[/tex]


[tex]3z=8y-4x-10[/tex]


[tex]z=\frac{8y-4x-10}{3}--(3)[/tex]


We substitute equation (3) into equation (2) and (1).


This implies that;


[tex]3x+4y-5\frac{(8y-4x-10)}{3}=-3[/tex]


We multiply through by 3 to get,

[tex]9x+12y-5(8y-4x-10)=-9[/tex]


We expand now to get,


[tex]9x+12y-40y+20x+50=-9[/tex]


[tex]29x-28y=-59--(4)[/tex]


We now put equation 3 in 2


[tex]-5x-2y+6\frac{(8y-4x-10)}{3}=5[/tex]

This gives us,

[tex]-5x-2y+2(8y-4x-10)=5[/tex]


We expand to obtain;


[tex]-5x-2y+16y-8x-20=5[/tex]


[tex]-13x+14y=25---(5)[/tex]


We nw solve equation (5) an (4) simultaneously.


Let us multiply equation (5) by 2 to get,

[tex]-26x+28y=50---(6)[/tex]


We add equation (6) and (4) to obtain,


[tex]3x=-9[/tex]



[tex]\Rightarrow x=-3[/tex]


We substitute the value of [tex]x[/tex] in to equation (5)


[tex]-13(-3)+14y=25[/tex]


[tex]39+14y=25[/tex]


[tex]14y=25-39[/tex]


[tex]14y=-14[/tex]


[tex]y=-1[/tex]


This implies that,



[tex]z=\frac{8(-1)-4(-3)-10}{3}[/tex]


[tex]z=\frac{-8+12-10}{3}[/tex]


[tex]z=\frac{-6}{3}[/tex]


[tex]z=-2[/tex]


[tex]x=-3,y=-1,z=-2[/tex]


The correct answer is B.








Alternatively


[tex]3x+4y-5z=-3--(1)[/tex]

[tex]-5x-2y+6z=5--(2)[/tex]

[tex]4x-8y+3z=-10--(3)[/tex]


We multiply equation (1) by 2 to get,

[tex]6x+8y-10z=-6 --(4)[/tex]


We multiply equation (2) by 4,


[tex]-20x-8y+24z=20--(5)[/tex]


Equation (3)-(5)


[tex]24x-21z=-30--(6)[/tex]


Equation (4) + (3)


[tex]10x-7z=-16--(7)[/tex]


We solve (7) and (60 simultaneously.


Multiply equation 7 by (3)


[tex]30x-21z=-48--(8)[/tex]


Equation (6) -(8)

[tex]-6x=18[/tex]


[tex]x=-3[/tex]

This implies,

[tex]10(-3)-7z=-16[/tex]


[tex]-30-7z=-16[/tex]


[tex]-7z=-16+30[/tex]


[tex]-7z=14[/tex]


[tex]z=-2[/tex]


[tex]3(-3)+4y-5(-2)=-3[/tex]


[tex]-9+4y+10=-3[/tex]


[tex]4y+1=-3[/tex]


[tex]4y=-4[/tex]


[tex]y=-1[/tex]


The solution is

[tex]x=-3,y=-1,z=-2[/tex]









I would do linear combinations

looking at the coeffients, I would cancel y first

multiply 2nd equation by 2 and add the 1st equation to it to get

-7x+0y+7z=7

-7x+7z=7


multiply first equation by 2 and add it to the last equation to get

10x+0y-7z=-16

10x-7z=-16


we now consider the 2 equations

-7x+7z=7 and

10x-7z=-16

add them together

3x+0z=-9

3x=-9

x=-3

sub back

-7x+7z=7

-7(-3)+7z=7

21+7z=7

7z=-14

z=-2


sub back


3x+4y-5z=-3

3(-3)+4y-5(-2)=-3

-9+4y+10=-3

4y=-4

y=-1


(x,y,z)=(-3,-1,-2)


ACCESS MORE